2021
DOI: 10.1371/journal.pone.0257893
|View full text |Cite|
|
Sign up to set email alerts
|

Morpho-physiological and biochemical attributes of Chili (Capsicum annum L.) genotypes grown under varying salinity levels

Abstract: Climate change is causing soil salinization, resulting in huge crop losses throughout the world. Multiple physiological and biochemical pathways determine the ability of plants to tolerate salt stress. Chili (Capsicum annum L.) is a salt-susceptible crop; therefore, its growth and yield is negatively impacted by salinity. Irreversible damage at cell level and photo inhibition due to high production of reactive oxygen species (ROS) and less CO2 availability caused by water stress is directly linked with salinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…The decreased growth traits under higher drought stress level can be explained with the lower moisture availability and subsequent lower transport of photosynthate from source to the sink. The differences among genotypes are owed to their inherent genetic makeup [41,42].…”
Section: Plos Onementioning
confidence: 99%
“…The decreased growth traits under higher drought stress level can be explained with the lower moisture availability and subsequent lower transport of photosynthate from source to the sink. The differences among genotypes are owed to their inherent genetic makeup [41,42].…”
Section: Plos Onementioning
confidence: 99%
“…Sweet bell pepper is among the most important cultivated horticultural species globally, with production increasing from 17 to 36 million tons over the past 20 years and a corresponding expansion in cultivated areas by approximately 35 % [ 12 , 13 ]. Previous studies, such as Shaid et al (2018) and [ 14 ]; have identified pepper plants as sensitive to salinity, with a tolerance limit of up to 1.5–2 dS m −1 . Each additional electrical conductivity (EC) unit beyond this threshold led to a 14 % decrease in pepper biomass production, and prolonged exposure to high salinity levels resulted in plant death [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an energy store, proline in its free state plays an important role in stabilizing the structure of biological macromolecules, removing ammonia toxicity and regulating the redox potential of plants under salt stress [23]. Previous studies have shown that foliar spraying with proline can stimulate plant root growth and contribute to an improved dry/fresh weight, photosynthetic rate, and antioxidant enzyme activities in chili (Capsicum annum L.) under salt stress [24]. Soluble sugar is not only the material basis and energy of organic matter synthesis but also an important material in maintaining the osmotic balance of plants under abiotic stress conditions [18].…”
Section: Introductionmentioning
confidence: 99%